Dampak output GDP sektor pertanian terhadap masalah pembangunan ekonomi di Indonesia (kemiskinan dan pengangguran) - Mustika, Candra; Emilia, Emilia (Jurnal Paradigma Ekonomika, 2018)
This study aims to analyze the development of agricultural GDP output and poverty and unemployment during the period 1993 – 2014 and analyze the effect of the GDP Output of the agricultural sector on the level of poverty and unemployment in Indonesia in that period. The results showed that during the period of 1993-2014 the data on gross domestic product (GDP) originating from the agricultural sector continued to fluctuate in the increase and decrease, the average GDP value of the agricultural sector is 496.9 trillion with an average value of 17%. The regression results in the first model show that agricultural sector GDP does not have a significant effect on poverty and the regression results in the second model show that agricultural GDP does not have a significant effect on the number of unemployed people in Indonesia